Deactivation resistance effect of alkane co-feeding on methane dehydroaromatization and active GaO+ species in Ga/HZSM-5 for BTX production. (1st October 2022) - Lee, Hyun Min; Lee, Byung Jin; Kim, Sang Yun; Kim, Do Heui; Han, Geun-Ho; Lee, Kwan-Young
Graphical abstract: Co-dehydroaromatization effect of natural gas achieves high aromatic formation than co-fed alkane and methane by suppressing deactivation process, and Ga ions (Ga 3+ or GaO) substituting acid sites (Al 3+ ) is beneficial for high BTX yield. Highlights: Natural gas co-dehydroaromatization study was implemented over Ga/HZSM-5 catalysts. Natural gas showed less pore plugging than co-fed alkanes or methane. Less pore plugging on the external surface improved coke resistance and BTX yield. 3 wt% Ga/HZSM-5 showed the highest GaO +, resulting in the best aromatic production. Abstract: An alternative feedstock is urgently required to produce valuable aromatic compounds due to the growing demand for chemicals, drastic fluctuations in crude oil supply, and especially recent oil prices. Hence, in this study, as an alternative potential production for aromatic compounds, the codehydroaromatization of natural gas (mol ratio of CH4 :C2 H6 :C3 H8 = 85:10:5) was investigated over Ga/HZSM-5 catalysts at a relatively low temperature of 650 °C. The optimal amount of Ga loading was found to be 3 wt% for the highest aromatic formation. Profound characterizations revealed that the selective formation of GaO + (Ga 3+ ) is crucial to obtaining more aromatics from the natural gas feed. In addition, since methane is a significantly stable chemical, formidable energy consumption is necessary to progress reactions. The effect of light hydrocarbon co-feeding ( i.e., ethane and propane) on the dehydroaromatization of methane was investigated, which resulted in methane activation at low temperatures from the natural gas composition. As a result, the aromatics formation rate in the natural gas feed was 1.5 times higher compared to the alkane co-feed (ethane and propane) and was incomparable to methane sole feed. It was demonstrated that the high aromatic formation rate resulted from the suppression of coke deposition on the external surface of the zeolite, thereby prolonging the catalytic activity. Therefore, the investigation of the codehydroaromatization of natural gas and optimal Ga loading synergistically enhances the potential of the direct use of natural gas in petrochemical industries.